2017
DOI: 10.1155/2017/3589271
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Modulators of Neuroplasticity: How Physical Activity, Mental Engagement, and Diet Promote Cognitive Health during Aging

Abstract: The number of the elderly across the globe will approximate 2.1 billion by 2050. Juxtaposed against this burgeoning segment of the population is evidence that nonpathological aging is associated with an increased risk for cognitive decline in a variety of domains, changes that can cause mild disability even before the onset of dementia. Given that pharmacological treatments that mitigate dementia are still outstanding, alternative therapeutic options are being investigated increasingly. The results from transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
128
0
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(146 citation statements)
references
References 370 publications
(346 reference statements)
3
128
0
15
Order By: Relevance
“…However, diet and nutrients may influence several biological pathways that are dysregulated in BD but relevant to cognition, such as monoaminergic activity, inflammation, oxidative stress, neuroplasticity and the gut microbiome . Growing preclinical and clinical evidence has shown that diet and physical activity are key to maintaining brain health and cognitive function, especially during ageing . Nutritional factors in particular, may stimulate adult neurogenesis and help to protect cognitive function in the elderly, as well as those with brain disorders .…”
Section: Emerging Correlates Of Cognitive Impairment In Bdmentioning
confidence: 99%
“…However, diet and nutrients may influence several biological pathways that are dysregulated in BD but relevant to cognition, such as monoaminergic activity, inflammation, oxidative stress, neuroplasticity and the gut microbiome . Growing preclinical and clinical evidence has shown that diet and physical activity are key to maintaining brain health and cognitive function, especially during ageing . Nutritional factors in particular, may stimulate adult neurogenesis and help to protect cognitive function in the elderly, as well as those with brain disorders .…”
Section: Emerging Correlates Of Cognitive Impairment In Bdmentioning
confidence: 99%
“…Furthermore, we should make efforts to improve the quality of care, and to seek a cure. Primary prevention could be focused on beneficial interventions, such as physical activity, mental engagement and diet, to promote slowing of the progression of dementia in the older community . Researchers also need to pay attention to the relationship between cardiovascular diseases and dementia.…”
Section: Discussionmentioning
confidence: 99%
“…Thus it prevents protein disulfide isomerase‐resistant misfolded protein forms that accumulate with oxidative stress that are implicated in the pathogenesis of AD (Howes & Perry, ). Relevant to both cognitive functions in ageing and dementia, curcumin rescued age‐related loss of hippocampal synapse input specificity of LTP via favouring NMDA receptor activity (Phillips, ). With respect to the suggested link between hypercholesterolaemia and AD risk, the hypocholesterolaemic effects of curcumin, as observed in different animal studies, have also been suggested as an additional basis to reduce dementia risk and cognitive decline with ageing (Goozee et al, ).…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%
“…‐Reverses age‐related loss of hippocampal synapse input specificity of LTP via favouring NMDA receptor activity (Phillips, )…”
Section: Phytochemicals As Nutraceuticalsmentioning
confidence: 99%
See 1 more Smart Citation